Electrolyte and electrochemical device
By modifying grain boundary of high-nickel positive electrode materials and adding protective additives, the problem of particle breakage during high-temperature cycles is solved, which significantly improves the high-temperature storage and circulation performance of the battery and reduces the risk of gas production.
Patent Information
- Application Number
- CN202110324283.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2020-03-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2040-03-27
AI Technical Summary
High-nickel positive electrode materials are prone to particle breakage during high-temperature cycles, resulting in increased battery load transfer impedance, rapid attenuation of circulation capacity, and safety hazards.
Spherical secondary particles are used to improve nickel-rich NCM positive electrode grain boundary modification, combined with the addition of appropriate protective additives (such as compounds of formula I and LiPO2F2), or mixing primary particles with secondary particles to improve particle breakage and optimize the high-temperature storage performance of the battery through additives in the electrolyte.
It significantly improves the battery's high-temperature storage performance and high-temperature circulation performance, suppresses high-temperature circulation gas production, and extends the battery's cycle life.
Smart Images

Figure CN113078361B_ABST
Abstract
Description
[0001] This application is a divisional application of an application with a filing date of March 27, 2020, application number 202010233604.6, and invention name “An electrolyte and an electrochemical device”. Technical Field
[0002] The present application relates to the field of energy storage technology, and in particular to an electrolyte and an electrochemical device containing the electrolyte. Background Art
[0003] As a chemical power source, lithium-ion batteries have the advantages of high energy density, high operating voltage, light weight, low self-discharge rate, long cycle life, no memory effect, and environmental friendliness. They are widely used in smart products (including mobile phones, notebooks, cameras and other electronic products), electric vehicles, power tools, drones, intelligent robots, advanced weapons and equipment, and large-scale energy storage. However, with the rapid development of information and communication technology and the diversity of market demand, people have also put forward more requirements and challenges for the power supply of electronic products, such as thinner, lighter, more diverse shapes, higher volume energy density and mass energy density, higher safety, higher power, etc. Summary of the invention
[0004] The present invention provides an electrolyte and an electrochemical device which can improve high temperature cycle performance, high temperature storage performance and have higher safety performance.
[0005] The present invention provides an electrochemical device, which comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises a current collector and a positive electrode active material layer, and the positive electrode active material layer comprises a positive electrode active material;
[0006] The electrolyte contains a compound of formula I: , where R 11 , R 12 , R 13 , R 14 , R 15 and R 16 Each is independently selected from: H, halogen, substituted or unsubstituted groups: C 1-8 Alkyl, C 2-8 Alkenyl, C 2-8 Alkynyl, or C 6-12 and the amount of the compound of formula I required per 1g of the positive electrode active material is about 0.001g to about 0.064g.
[0007] In some embodiments, the compound of formula I comprises at least one of the following compounds: .
[0008] In some embodiments, the positive electrode active material layer comprises first particles, the circularity of the first particles is 0.4 to 1, and the cross-sectional area of the first particles is not less than 20 square microns calculated based on the cross-sectional area of the positive electrode perpendicular to the current collector, and the sum of the cross-sectional areas of the first particles accounts for 5% to 50%.
[0009] In some embodiments, the positive electrode active material layer comprises second particles, the circularity of the second particles is less than 0.4, and the cross-sectional area of the second particles is smaller than the cross-sectional area of the first particles, calculated based on the cross-sectional area of the positive electrode perpendicular to the current collector.
[0010] In some embodiments, based on the cross-sectional area of the positive electrode perpendicular to the current collector, the sum of the cross-sectional areas of the second particles accounts for 5% to 60%.
[0011] In some embodiments, the electrolyte further comprises an additive A, and the additive A comprises at least one of lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium 4,5-dicyano-2-trifluoromethylimidazole, lithium difluorobis(oxalato)phosphate, lithium difluorooxalatoborate, or lithium bis(oxalatoborate).
[0012] In some embodiments, 0.000026 g to 0.019 g of the additive A is required per 1 g of the positive electrode active material.
[0013] In some embodiments, the electrolyte further comprises an additive B, and the additive B comprises at least one of vinylene carbonate (VC), fluoroethylene carbonate (FEC), diethylene sulfate (DTD), tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), adiponitrile (ADN), succinonitrile (SN), 1,3,5-pentanetricarboxylic acid nitrile, 1,3,6-hexanetricarboxylic acid nitrile (HTCN), 1,2,6-hexanetricarboxylic acid nitrile or 1,2,3-tris(2-cyano)propane (TECP).
[0014] In some embodiments, the mass ratio of the compound of formula I to the additive B is about 7:1 to about 1:7.
[0015] In some embodiments, 0.0001 g to 0.2 g of the additive B is required per 1 g of the positive electrode active material.
[0016] In some embodiments, the positive electrode active material layer comprises a phosphorus-containing compound, the phosphorus-containing compound comprises at least one of Li3PO4 or LiMPO4, wherein M is selected from at least one of Co, Mn or Fe.
[0017] In some embodiments, the phosphorus-containing compound is included on the surface or at the grain boundary of the positive electrode active material.
[0018] In some embodiments, the positive electrode active material comprises LiNi x Co y Mn z O2, of which 0.55 <x<0.92,0.03<y<0.2,0.04<z<0.3。
[0019] In some embodiments, the positive electrode active material comprises a Q element, wherein Q is selected from at least one of Zr, Ti, Yr, V, Al, Mg, or Sn.
[0020] In some embodiments, the porosity of the positive electrode is ≤25%.
[0021] In some embodiments, based on the cross-sectional area of the positive electrode perpendicular to the current collector, the cross-sectional area of the positive electrode current collector accounts for 5% to 20%.
[0022] In some embodiments, the compaction density of the positive electrode active material layer is less than or equal to 3.6 g / cm 3 .
[0023] In some embodiments, the electrolyte further comprises a compound of formula II , where R 31 and R 32 Each independently selected from substituted or unsubstituted C 1-10 Alkyl, or substituted or unsubstituted C 2-8 The alkenyl group, wherein substituted means substituted with one or more halogens, and the content of the compound of formula II is about 0.5 wt % to about 50 wt % based on the total weight of the electrolyte.
[0024] In some embodiments, the compound of formula II comprises at least one of the following compounds: .
[0025] Yet another aspect of the present invention provides an electronic device, comprising any one of the electrochemical devices described above.
[0026] Additional aspects and advantages of the embodiments of the present application will be described in part in the subsequent description or explained through the implementation of the embodiments of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 An electron micrograph of a positive electrode active material according to an embodiment of the present application is shown. DETAILED DESCRIPTION
[0028] The embodiments of the present application will be described in detail below. The embodiments of the present application should not be interpreted as limiting the scope of protection claimed in the present application. Unless otherwise clearly indicated, the following terms used herein have the meanings indicated below.
[0029] As used herein, the term "about" is used to describe and illustrate small changes. When used in conjunction with an event or situation, the term may refer to an example in which the event or situation occurs precisely and an example in which the event or situation occurs very approximately. For example, when used in conjunction with a numerical value, the term may refer to a range of variation of less than or equal to ±10% of the numerical value, such as less than or equal to ±5%, less than or equal to ±4%, less than or equal to ±3%, less than or equal to ±2%, less than or equal to ±1%, less than or equal to ±0.5%, less than or equal to ±0.1%, or less than or equal to ±0.05%. In addition, amounts, ratios, and other numerical values are sometimes presented in this article in a range format. It should be understood that such a range format is for convenience and simplicity, and should be flexibly understood to include not only numerical values explicitly designated as range limits, but also all individual numerical values or subranges encompassed within the range, as if each numerical value and subrange were explicitly designated.
[0030] In the detailed description and claims, a list of items connected by the term "one of" can mean any of the listed items. For example, if items A and B are listed, the phrase "one of A and B" means only A or only B. In another example, if items A, B, and C are listed, the phrase "one of A, B, and C" means only A; only B; or only C. Item A can include a single element or multiple elements. Item B can include a single element or multiple elements. Item C can include a single element or multiple elements.
[0031] In the detailed description and claims, a list of items connected by the terms "at least one of," "at least one of," or other similar terms may mean any combination of the listed items. For example, if items A and B are listed, the phrase "at least one of A and B" or "at least one of A or B" means only A; only B; or A and B. In another example, if items A, B, and C are listed, the phrase "at least one of A, B, and C" or "at least one of A, B, or C" means only A; or only B; only C; A and B (excluding C); A and C (excluding B); B and C (excluding A); or all of A, B, and C. Item A may include a single element or multiple elements. Item B may include a single element or multiple elements. Item C may include a single element or multiple elements.
[0032] In the detailed description and claims, the number after the capital letter "C" is used to represent the carbon number, such as "C1-C 10 ”, “C3-C 10 ”, etc., the number after “C”, such as “1”, “3” or “10”, indicates the number of carbon atoms in the specific functional group. That is, the functional group may include 1-10 carbon atoms and 3-10 carbon atoms, respectively. For example, “C1-C4 alkyl” or “C 1-4 "Alkyl" refers to an alkyl group having 1 to 4 carbon atoms, for example, CH3-, CH3CH2-, CH3CH2CH2-, (CH3)2CH-, CH3CH2CH2CH2-, CH3CH2CH(CH3)- or (CH3)3C-.
[0033] As used herein, the term "alkyl" refers to a straight chain saturated hydrocarbon structure having 1 to 10 carbon atoms. "Alkyl" is also intended to be a branched or cyclic hydrocarbon structure having 3 to 10 carbon atoms. For example, the alkyl group may be an alkyl group having 1 to 10 carbon atoms, an alkyl group having 1 to 8 carbon atoms, an alkyl group having 1 to 6 carbon atoms, or an alkyl group having 1 to 4 carbon atoms. When specifying an alkyl group having a specific carbon number, it is intended to cover all geometric isomers having that carbon number; therefore, for example, "butyl" means to include n-butyl, sec-butyl, isobutyl, tert-butyl and cyclobutyl; "propyl" includes n-propyl, isopropyl and cyclopropyl. Examples of alkyl groups include, but are not limited to, methyl, ethyl, n-propyl, isopropyl, cyclopropyl, n-butyl, isobutyl, sec-butyl, tert-butyl, cyclobutyl, n-pentyl, isopentyl, neopentyl, cyclopentyl, methylcyclopentyl, ethylcyclopentyl, n-hexyl, isohexyl, cyclohexyl, n-heptyl, octyl, cyclopropyl, cyclobutyl, norbornyl, etc. In addition, the alkyl group may be optionally substituted.
[0034] The term "alkenyl" refers to a monovalent unsaturated hydrocarbon group that may be straight or branched and has at least one and typically 1, 2 or 3 carbon-carbon double bonds. Unless otherwise defined, the alkenyl typically contains 2-10 carbon atoms, for example, 2-8 carbon atoms, 2-6 carbon atoms, or 2-4 carbon atoms. Representative alkenyls include, for example, vinyl, n-propenyl, isopropenyl, n-but-2-enyl, but-3-enyl, n-hex-3-enyl, etc. In addition, the alkenyl may be optionally substituted.
[0035] The term "alkynyl" refers to a monovalent unsaturated hydrocarbon group that may be straight or branched and has at least one and typically 1, 2 or 3 carbon-carbon triple bonds. Unless otherwise defined, the alkynyl group typically contains 2 to 10, 2 to 8, 2 to 6, or 2 to 4 carbon atoms. Representative alkynyl groups include, for example, ethynyl, prop-2-ynyl (n-propynyl), n-but-2-ynyl, n-hex-3-ynyl, and the like. In addition, the alkynyl group may be optionally substituted.
[0036] The term "aryl" encompasses monocyclic and polycyclic systems. Polycyclic rings may have two or more rings in which two carbons are common to two adjacent rings (the rings are "fused"), wherein at least one of the rings is aromatic, for example, the other rings may be cycloalkyl, cycloalkenyl, aryl, heterocycle and / or heteroaryl. For example, an aryl group may contain 6 to 12 carbon atoms or 6 to 10 carbon atoms. Representative aryl groups include, for example, phenyl, methylphenyl, propylphenyl, isopropylphenyl, benzyl and naphthalene-1-yl, naphthalene-2-yl, and the like. In addition, an aryl group may be optionally substituted.
[0037] When the above substituents are substituted, unless otherwise stated, they are substituted with one or more halogens.
[0038] As used herein, the term "halogen" encompasses F, Cl, Br and I, preferably F or Cl.
[0039] The term "circularity" or "sphericity" refers to the degree to which the cross section of a particle is close to a theoretical circle. Circularity R = (4π × area) / (circumference × circumference). When R is 1, the shape is a circle; the smaller R is, the more irregular the shape is, and the greater the difference from a circle. This application uses a roundness meter to measure the circularity of the positive electrode active material particles. The specific test method can be found in the following specific embodiments.
[0040] The term "broken particles" refers to continuous lines with a length of not less than 0.1 micron and a width of not less than 0.01 micron in the cross section of the particles in the image under a scanning electron microscope, which are regarded as cracks, and particles with cracks are regarded as broken particles.
[0041] The term "positive electrode active material" refers to a material that can reversibly intercalate and deintercalate lithium ions. In some embodiments of the present application, the positive electrode active material includes, but is not limited to, lithium-containing transition metal oxides.
[0042] Means for increasing the energy density of lithium-ion batteries include two aspects: one is to use a negative electrode material with an intercalation / deintercalation lithium voltage platform close to that of the graphite negative electrode but with a significantly higher specific capacity than the graphite negative electrode, such as Si / C composite materials or SiO x / C composite materials; the other is to develop positive electrode materials with higher specific energy, including lithium-rich and manganese-rich positive electrodes (such as xLi2MnO3·(1-x)LiMO2, 0 < x < 1, M is one or more of Ni, Co, Mn, Fe, Ru, or Sn), high-nickel positive electrodes (such as LiNi x Co y Mn z O2 (NCM), 0.5 ≤ x < 1, 0 < y ≤ 0.2, 0 < z ≤ 0.3), etc. Among them, spherical secondary particle high-nickel ternary positive electrode materials (LiNi x Co y Mn z O2(NCM), 0.5 ≤ x < 1, 0 < y ≤ 0.2, 0 < z ≤ 0.3) have begun to be widely used in high-energy density lithium-ion batteries due to their good particle fluidity, high tap density, and high mass specific energy. However, the inventors of the present application have found through research that during the high-voltage charging process of spherical secondary particle high-nickel ternary positive electrodes, when the lithium deintercalation amount reaches more than 80%, the lattice of the material shrinks anisotropically, resulting in a sharp increase in internal stress in the particles. The secondary particles break during repeated cycling, and the physical contact between the primary particles is severely damaged, leading to a sharp increase in the charge transfer impedance of the battery and a rapid capacity decay in the later stage of cycling; in addition, after the secondary particles break, the electrolyte quickly penetrates into the interior of the secondary particles, and many side reactions occur between the electrolyte and the primary particles. Especially during high-temperature cycling, safety hazards such as gas swelling occur in the battery cycle. In order to improve the cycling performance of the nickel-rich material battery system and suppress cycling gas generation, the present invention uses, for example, spherical secondary particle high-nickel NCM positive electrode grain boundary modification to suppress particle breakage, and at the same time combines the addition of appropriate protective additives (such as Compound I and LiPO2F2, etc.), or, for example, uses a mixture of primary particles and secondary particles to improve particle breakage, and at the same time combines the addition of appropriate protective additives (such as Compound I and LiPO2F2, etc.). These combinations can significantly improve the high-temperature storage performance, high-temperature cycling performance, and suppress high-temperature cycling gas generation of the battery.
[0043] I. Electrochemical device
[0044] The electrochemical device of the present application includes any device in which an electrochemical reaction occurs, and its specific examples include all kinds of primary batteries, secondary batteries, fuel cells, solar cells or capacitors. In particular, the electrochemical device is a lithium secondary battery, including a lithium metal secondary battery, a lithium ion secondary battery, a lithium polymer secondary battery or a lithium ion polymer secondary battery. In some embodiments, the electrochemical device of the present application includes a positive electrode, a negative electrode, a separator, and an electrolyte.
[0045] positive electrode
[0046] In some embodiments, the positive electrode includes a current collector and a positive electrode active material layer on the current collector, wherein the positive electrode active material layer includes a positive electrode active material.
[0047] The positive electrode active material includes at least one lithiated intercalation compound that reversibly intercalates and deintercalates lithium ions. In some embodiments of the present application, the positive electrode active material includes a lithium-containing transition metal oxide. In some embodiments, the positive electrode active material includes a composite oxide. In some embodiments, the composite oxide contains lithium and at least one element selected from cobalt, manganese and nickel.
[0048] In some embodiments, the positive electrode active material layer comprises a phosphorus-containing compound, the phosphorus-containing compound comprises at least one of Li3PO4 or LiMPO4, wherein M comprises at least one of Co, Mn or Fe.
[0049] In some embodiments, the phosphorus-containing compound is included on the surface or at the grain boundary of the positive electrode active material.
[0050] In some embodiments, the positive electrode active material comprises LiNi x Co y Mn z O2, of which 0.55 <x<0.92,0.03<y<0.2,0.04<z<0.3。
[0051] In some embodiments, the positive electrode active material comprises a Q element, wherein Q is selected from at least one of Zr, Ti, Yr, V, Al, Mg, or Sn.
[0052] The inventors have found that in the nickel-containing ternary material of the positive electrode active material, the main role of the nickel element is to improve the energy density. In the same charge and discharge voltage range, the higher the nickel content, the higher the gram capacity. However, in the actual application of high-nickel materials in electrochemical devices, the high-nickel materials have a high amount of lithium removal at the same voltage, and the unit cell volume expands and shrinks greatly, which causes the particles to be easily broken and easily react with the electrolyte. After the particles are broken, new interfaces will be exposed, causing the electrolyte to penetrate into the interior of the particles through cracks and react with the positive electrode active material at the new interface, aggravating the occurrence of gas production and causing the capacity of the electrochemical device to decay rapidly with the progress of the charge and discharge cycle. In addition, during the charging process of the electrochemical device, as lithium ions are continuously released from the positive electrode active material, the binding force between the active metal (e.g., nickel element) in the positive electrode active material and oxygen is weakened, oxygen is released, and the released oxygen will oxidize the electrolyte, aggravating gas production. The above problems seriously limit the application of high-nickel materials in high energy density electrochemical devices (especially in the positive electrode active material LiNi x Co y Mn z O2, when x ≥ 0.6).
[0053] The first particle is a collection of many single crystal particles, wherein the single crystal is a crystal in which the particles inside are regularly and periodically arranged in three-dimensional space. The morphology of the first particle is spherical or ellipsoidal, with a large roundness and a large cross-sectional area. The second particle is a collection of single crystals with larger grain size.
[0054] In some embodiments, the positive electrode active material layer comprises first particles, the circularity of the first particles is 0.4 to 1, and the cross-sectional area of the first particles is not less than 20 square microns calculated based on the cross-sectional area of the positive electrode perpendicular to the current collector, and the sum of the cross-sectional areas of the first particles accounts for 5% to 50%.
[0055] In some embodiments, the first particles have a specific surface area (BET) of about 0.14 m 2 / g to about 0.95 m 2 / g;
[0056] In some embodiments, the first particles have a Dv50 of about 5.5 microns to about 14.5 microns and a Dv90 of less than or equal to 18 microns.
[0057] In some embodiments, the positive electrode active material layer comprises second particles, the circularity of the second particles is less than 0.4, and the cross-sectional area of the second particles is smaller than the cross-sectional area of the first particles, calculated based on the cross-sectional area of the positive electrode perpendicular to the current collector.
[0058] In some embodiments, based on the cross-sectional area of the positive electrode perpendicular to the current collector, the sum of the cross-sectional areas of the second particles accounts for 5% to 60%.
[0059] In some embodiments, the porosity of the positive electrode is ≤25%.
[0060] In some embodiments, based on the cross-sectional area of the positive electrode perpendicular to the current collector, the cross-sectional area of the positive electrode current collector accounts for 5% to 20%.
[0061] In some embodiments, the compaction density of the positive electrode active material layer is less than or equal to about 3.6 g / cm 3 .
[0062] In some embodiments, the positive electrode active material comprises a nickel-rich positive electrode material modified by Li3PO4 or consists of a nickel-rich positive electrode material modified by Li3PO4, and its preparation method can be exemplified by the following two methods:
[0063] Liquid phase mixing method: the positive electrode material (LiNi 0.84 Co 0.13 Mn 0.06 O2) and H3PO4 are dispersed in an ethanol solution, and then magnetically stirred for 60 minutes, and then transferred to an 80°C oil bath and stirred until the ethanol is completely evaporated to obtain a Li3PO4-modified ternary positive electrode active material. The positive electrode active materials with different particle sizes are obtained by crushing and sieve screening, so that the obtained Li3PO4 content accounts for about 1 weight % of the total weight of the modified nickel-rich ternary positive electrode material.
[0064] Sol-gel method: the positive electrode material (LiNi 0.84 Co 0.13 Mn 0.06 O2) was added to an ethanol solution containing lithium nitrate, citric acid and phosphoric acid, and stirred vigorously to make the mass ratio of the positive electrode material to Li3PO4 99:1. Then it was heated to 80°C and stirred continuously until the solvent evaporated completely, and finally calcined in an air atmosphere at 600°C for 2 hours to obtain a Li3PO4-modified positive electrode material.
[0065] In some embodiments, the positive electrode active material comprises a nickel-rich positive electrode material modified by LiMPO4 or consists of a nickel-rich positive electrode material modified by Li3MO4, and its preparation method is similar to the preparation method of the nickel-rich positive electrode material modified by Li3PO4.
[0066] In some embodiments, the positive electrode active material may have a coating on its surface, or may be mixed with another compound having a coating. The coating may include at least one coating element compound selected from an oxide of a coating element, a hydroxide of a coating element, an oxyhydroxide of a coating element, an oxycarbonate of a coating element, and a hydroxycarbonate of a coating element. The compound for the coating may be amorphous or crystalline.
[0067] In some embodiments, the coating element contained in the coating may include Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr or any combination thereof. The coating may be applied by any method as long as the method does not adversely affect the performance of the positive electrode active material. For example, the method may include any coating method known in the art, such as spraying, dipping, etc.
[0068] The positive electrode active material layer also includes a binder, and optionally a conductive material. The binder improves the bonding of the positive electrode active material particles to each other and also improves the bonding of the positive electrode active material to the current collector.
[0069] In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0070] In some embodiments, the conductive material includes, but is not limited to: carbon-based materials, metal-based materials, conductive polymers, and mixtures thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0071] In some embodiments, the current collector may be aluminum, but is not limited thereto.
[0072] The positive electrode can be prepared by a preparation method known in the art. For example, the positive electrode can be obtained by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and coating the active material composition on a current collector. In some embodiments, the solvent may include N-methylpyrrolidone, etc., but is not limited thereto.
[0073] In some embodiments, the positive electrode is made by forming a positive electrode material using a positive electrode active material layer including a lithium transition metal compound powder and a binder on a current collector.
[0074] In some embodiments, the positive electrode active material layer can generally be prepared by the following operations: dry mixing the positive electrode material and the binder (conductive material and thickener used as needed) to form a sheet, pressing the obtained sheet to the positive electrode collector, or dissolving or dispersing these materials in a liquid medium to form a slurry, coating the slurry on the positive electrode collector and drying.
[0075] negative electrode
[0076] The material, composition and manufacturing method of the negative electrode used in the electrochemical device of the present application may include any technology disclosed in the prior art. In some embodiments, the negative electrode is a negative electrode described in US Patent Application US9812739B, which is incorporated into the present application by reference in its entirety.
[0077] In some embodiments, the negative electrode includes a current collector and a negative electrode active material layer located on the current collector. The negative electrode active material includes a material that reversibly embeds / deintercalates lithium ions. In some embodiments, the material that reversibly embeds / deintercalates lithium ions includes a carbon material. In some embodiments, the carbon material can be any carbon-based negative electrode active material commonly used in lithium-ion rechargeable batteries. In some embodiments, the carbon material includes, but is not limited to: crystalline carbon, amorphous carbon, or a mixture thereof. Crystalline carbon can be amorphous, flaky, flake-shaped, spherical or fibrous natural graphite or artificial graphite. Amorphous carbon can be soft carbon, hard carbon, mesophase pitch carbide, calcined coke, etc.
[0078] In some embodiments, the negative electrode active material layer includes a negative electrode active material. The specific types of negative electrode active materials are not subject to specific restrictions and can be selected according to needs. In some embodiments, the negative electrode active material includes, but is not limited to: lithium metal, structured lithium metal, natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structured lithiated TiO2-Li4Ti5O 12 , Li-Al alloy or any combination thereof. The silicon-carbon composite refers to a composite containing at least about 5 wt % silicon based on the weight of the silicon-carbon negative electrode active material.
[0079] When the negative electrode includes a silicon-carbon compound, based on the total weight of the negative electrode active material, silicon: carbon = about 1:10-10:1, and the median particle size D50 of the silicon-carbon compound is about 0.1 microns to 20 microns. When the negative electrode includes an alloy material, a negative electrode active material layer can be formed using a method such as evaporation, sputtering, and plating. When the negative electrode includes lithium metal, the negative electrode active material layer is formed, for example, using a spherical twisted conductive skeleton and metal particles dispersed in the conductive skeleton. In some embodiments, the spherical twisted conductive skeleton may have a porosity of about 5% to about 85%. In some embodiments, a protective layer may also be provided on the lithium metal negative electrode active material layer.
[0080] In some embodiments, the negative electrode active material layer may include a binder and optionally a conductive material. The binder improves the bonding between the negative electrode active material particles and the bonding between the negative electrode active material and the current collector. In some embodiments, the binder includes, but is not limited to: polyvinyl alcohol, carboxymethyl cellulose, hydroxypropyl cellulose, diacetyl cellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, ethylene oxide-containing polymers, polyvinyl pyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene 1,1-difluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc.
[0081] In some embodiments, the conductive material includes, but is not limited to: a carbon-based material, a metal-based material, a conductive polymer, or a mixture thereof. In some embodiments, the carbon-based material is selected from natural graphite, artificial graphite, carbon black, acetylene black, Ketjen black, carbon fiber, or any combination thereof. In some embodiments, the metal-based material is selected from metal powder, metal fiber, copper, nickel, aluminum, silver. In some embodiments, the conductive polymer is a polyphenylene derivative.
[0082] In some embodiments, the current collector includes, but is not limited to, copper foil, nickel foil, stainless steel foil, titanium foil, nickel foam, copper foam, a polymer substrate coated with a conductive metal, and any combination thereof.
[0083] The negative electrode can be prepared by a preparation method known in the art. For example, the negative electrode can be obtained by mixing an active material, a conductive material, and a binder in a solvent to prepare an active material composition, and coating the active material composition on a current collector. In some embodiments, the solvent may include water, etc., but is not limited thereto.
[0084] Isolation film
[0085] In some embodiments, the electrochemical device of the present application is provided with a separator between the positive electrode and the negative electrode to prevent short circuit. The material and shape of the separator used in the electrochemical device of the present application are not particularly limited, and it can be any technology disclosed in the prior art. In some embodiments, the separator includes a polymer or inorganic substance formed of a material that is stable to the electrolyte of the present application.
[0086] For example, the isolation membrane may include a substrate layer and a surface treatment layer. The substrate layer is a non-woven fabric, a film or a composite film having a porous structure, and the material of the substrate layer is selected from at least one of polyethylene, polypropylene, polyethylene terephthalate and polyimide. Specifically, a polypropylene porous film, a polyethylene porous film, a polypropylene non-woven fabric, a polyethylene non-woven fabric or a polypropylene-polyethylene-polypropylene porous composite film may be selected. The substrate layer may be one or more layers. When the substrate layer is multi-layered, the composition of the polymers of different substrate layers may be the same or different, and the weight average molecular weight of the polymers of different substrate layers is not completely the same; when the substrate layer is multi-layered, the closed-cell temperatures of the polymers of different substrate layers are different.
[0087] In some embodiments, a surface treatment layer is disposed on at least one surface of the substrate layer. The surface treatment layer may be a polymer layer or an inorganic layer, or a layer formed by mixing a polymer and an inorganic layer.
[0088] In some embodiments, the isolation membrane includes a porous substrate and a coating layer, and the coating layer includes inorganic particles and a binder.
[0089] In some embodiments, the coating layer has a thickness of about 0.5 micrometers to about 10 micrometers, about 1 micrometer to about 8 micrometers, or about 3 micrometers to about 5 micrometers.
[0090] In some embodiments, the inorganic particles are selected from at least one of SiO2, Al2O3, CaO, TiO2, ZnO2, MgO, ZrO2, SnO2, Al(OH)3, or AlOOH. In some embodiments, the inorganic particles have a particle size of about 0.001 microns to about 3 microns.
[0091] In some embodiments, the binder is selected from at least one of polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoroethylene copolymer (PVDF-HFP), polyvinyl pyrrolidone (PVP), polyacrylate, pure acrylic emulsion (anionic acrylic emulsion copolymerized by acrylic ester and special functional monomers), styrene acrylic emulsion (styrene-acrylate emulsion) obtained by emulsion copolymerization of styrene and acrylate monomers) and styrene-butadiene emulsion (SBR, obtained by copolymerization of butadiene and styrene emulsion).
[0092] Electrolyte
[0093] The electrochemical device of some embodiments of the present invention comprises a positive electrode, a negative electrode, a separator and an electrolyte, wherein the positive electrode comprises a current collector and a positive electrode active material layer, and the positive electrode active material layer comprises a positive electrode active material;
[0094] The electrolyte contains a compound of formula I: , where R 11 , R 12 , R 13 , R 14 , R 15 and R 16 Each is independently selected from: H, halogen, substituted or unsubstituted groups: C 1-8 Alkyl, C 2-8 Alkenyl, C 2-8 Alkynyl, or C 6-12 and the amount of the compound of formula I required per 1g of the positive electrode active material is about 0.001g to about 0.064g.
[0095] In some embodiments, R 11 , R 12 , R 13 , R 14 , R 15 and R 16 Each is independently selected from: H, halogen, substituted or unsubstituted groups: C 1-6 Alkyl or C 1-4 Alkyl, C 2-6 Alkenyl or C 2-4 Alkenyl, C 2-6 Alkynyl or C 2-4 Alkynyl, or C 6-10 Aryl.
[0096] In some embodiments, R 11 , R 12 , R 13 , R 14 , R 15 and R 16 Each is independently selected from: H, F, methyl, ethyl, propyl, isopropyl, vinyl, or -CF3.
[0097] In some embodiments, the amount of the compound of formula I required for each 1g of the positive electrode active material is about 0.01g to about 0.06g; in some embodiments, the amount of the compound of formula I required for each 1g of the positive electrode active material is about 0.015g, about 0.02g, about 0.025g, about 0.03g, about 0.035g, about 0.04g, about 0.045g, about 0.05g, or about 0.055g.
[0098] The inventors have found that the positive electrode material has particle breakage in the late stage of the cycle. The compound of formula I has good thermal stability and a moderate reaction rate. It can be continuously and slowly consumed during the cycle. After the material particles are broken, a protective layer is effectively formed on the surface of the material, which reduces the gas production problem caused by side reactions.
[0099] The inventors have also found that the film-forming impedance of the compound of formula I is relatively large. Combined with the P element modification on the surface of the positive electrode material, on the one hand, the stability and ion conductivity of the material itself can be improved, and on the other hand, the reaction of the compound of formula I in the early stage of the cycle can be reduced, the initial impedance can be reduced, and at the same time, the film-forming effect in the later stage of the cycle can be ensured, thereby further achieving the effect of improving the cycle and reducing gas production.
[0100] In some embodiments, the compound of formula I comprises at least one of the following compounds: .
[0101] In some embodiments, the electrolyte further comprises an additive A, wherein the additive A comprises at least one of lithium tetrafluoroborate (LiBF4), lithium difluorophosphate (LiPO2F2), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), 4,5-dicyano-2-trifluoromethylimidazolium lithium, lithium difluorobis(oxalate)phosphate, lithium difluorooxalatoborate, or lithium bis(oxalatoborate); and about 0.000026 g to about 0.019 g of the additive A is required for every 1 g of the positive electrode active material.
[0102] The inventors have found that additive A can preferentially form a film on the surface of the positive electrode material to form an interface film with relatively low impedance, reduce the side reactions of the electrolyte on the surface of the positive electrode material, and reduce the reaction of the compound of formula I in the early stage of the cycle, which can ensure the stability in the early stage of the cycle, improve the cycle capacity, and reduce the occurrence of gas production.
[0103] In some embodiments, the additive A comprises lithium difluorophosphate (LiPO 2 F 2 ).
[0104] In some embodiments, about 0.00003 g to 0.015 g of the additive A is required per 1 g of the positive electrode active material. In some embodiments, about 0.00006 g, about 0.00008 g, about 0.0001 g, about 0.0003 g, about 0.0005 g, about 0.0007 g, about 0.001 g, about 0.003 g, about 0.005 g, about 0.007 g, about 0.01 g, about 0.013 g, about 0.015 g, or about 0.017 g of the additive A is required per 1 g of the positive electrode active material.
[0105] In some embodiments, the electrolyte further comprises an additive B, wherein the additive B comprises vinylene carbonate (VC), fluoroethylene carbonate (FEC), diethylene sulfate (DTD), tris(trimethylsilyl) phosphate (TMSP), tris(trimethylsilyl) borate (TMSB), adiponitrile (ADN), succinonitrile (SN), 1,3,5-pentanetricarbonitrile, 1,3,6-hexanetricarbonitrile (HTCN), 1,2,6-hexanetricarbonitrile or 1,2,3-tris(2-cyano)propane (TECP).
[0106] In some embodiments, the mass ratio of the compound of formula I to the additive B is 7:1 to 1:7.
[0107] In some embodiments, 0.0001 g to 0.2 g of the additive B is required per 1 g of the positive electrode active material.
[0108] In some embodiments, the mass ratio of the compound of formula I to the additive B is about 7:1, about 6:1, about 5:1, about 4:1, about 3:1, about 2:1, about 1:1, about 1:2, about 1:3, about 1:4, about 1:5, about 1:6, or about 1:7.
[0109] In some embodiments, 0.0005 g to 0.18 g of the additive B is required per 1 g of the positive electrode active material. In some embodiments, about 0.0005 g, about 0.001 g, about 0.005 g, about 0.01 g, about 0.03 g, about 0.05 g, about 0.07 g, about 0.1 g, about 0.12 g, about 0.15 g, about 0.18 g of the additive B is required per 1 g of the positive electrode active material.
[0110] The inventors have found that additive B can form a film on the positive electrode, adjust the composition of the positive electrode film, and relatively increase the content of the organic layer, which can enhance the stability of the positive electrode film and further improve the cycle stability.
[0111] In some embodiments, the electrolyte further comprises a compound of formula II , where R 31 and R 32 Each independently selected from substituted or unsubstituted C 1-10 Alkyl, or substituted or unsubstituted C 2-8 The alkenyl group, wherein substituted means substituted with one or more halogens, and the content of the compound of formula II is about 0.5 wt % to about 50 wt % based on the total weight of the electrolyte.
[0112] In some embodiments, R 31 and R 32 Each is independently selected from the following substituted or unsubstituted groups: C 1-8Alkyl, C 1-6 Alkyl, C 1-4 Alkyl, C 2-6 Alkenyl, or C 2-4 Alkenyl wherein substituted refers to substitution by one or more halogens.
[0113] In some embodiments, R 31 and R 32 At least one of them is substituted with one or more halogens.
[0114] In some embodiments, R 31 and R 32 Each is independently selected from the following groups which are unsubstituted or substituted with one or more F: methyl, ethyl, propyl, isopropyl, vinyl, or propenyl; in some embodiments, R 31 and R 32 At least one of them is substituted with one or more F.
[0115] In some embodiments, the content of the compound of formula II is about 1 wt % to 45 wt % based on the total weight of the electrolyte. In some embodiments, the content of the compound of formula II is about 5 wt %, about 10 wt %, about 15 wt %, about 20 wt %, about 25 wt %, about 30 wt %, about 35 wt %, or about 40 wt % based on the total weight of the electrolyte.
[0116] In some embodiments, the compound of formula II comprises at least one of the following compounds: .
[0117] The inventors have found that the combination of the compound of formula I and the compound of formula II can reduce the ion transmission resistance and form a protective layer on the positive electrode. After particle breakage occurs in the late stage of the cycle, the compounds of formula I and formula II work together to effectively repair the protective layer on the positive electrode surface, thereby improving the cycle life.
[0118] In some embodiments, the electrolyte further includes a lithium salt and an organic solvent.
[0119] In some embodiments, the lithium salt is selected from one or more of an inorganic lithium salt and an organic lithium salt. In some embodiments, the lithium salt contains at least one of a fluorine element, a boron element, or a phosphorus element. In some embodiments, the lithium salt is selected from one or more of the following lithium salts: lithium hexafluorophosphate LiPF6, bistrifluoromethanesulfonyl imide lithium LiN(CF3SO2)2 (abbreviated as LiTFSI), bis(fluorosulfonyl)imide lithium Li(N(SO2F)2) (abbreviated as LiFSI), lithium hexafluoroarsenate LiAsF6, lithium perchlorate LiClO4, or lithium trifluoromethanesulfonate LiCF3SO3.
[0120] In some embodiments, the concentration of the lithium salt is 0.3 mol / L to 1.5 mol / L. In some embodiments, the concentration of the lithium salt is 0.5 mol / L to 1.3 mol / L or about 0.8 mol / L to 1.2 mol / L. In some embodiments, the concentration of the lithium salt is about 1.10 mol / L.
[0121] The organic solvent comprises at least one of ethylene carbonate (EC), propylene carbonate (PC), diethyl carbonate (DEC), ethyl methyl carbonate (DEC), dimethyl carbonate (DMC), sulfolane (SF), γ-butyrolactone (γ-BL), propylene carbonate, methyl formate (MF), ethyl formate (MA), ethyl acetate (EA), ethyl propionate (EP), propyl propionate (PP), methyl propionate, methyl butyrate, ethyl butyrate, fluoroethyl methyl carbonate, fluorodimethyl carbonate, or fluorodiethyl carbonate.
[0122] In some embodiments, the solvent accounts for 70 wt % to 95 wt % of the electrolyte.
[0123] The electrolyte used in the electrochemical device of the present application is any of the above-mentioned electrolytes of the present application. In addition, the electrolyte used in the electrochemical device of the present application may also include other electrolytes within the scope not departing from the gist of the present application.
[0124] 2. Application
[0125] The use of the electrochemical device of the present application is not particularly limited, and can be used for various known uses, such as laptop computers, pen-input computers, mobile computers, electronic book players, portable phones, portable fax machines, portable copiers, portable printers, head-mounted stereo headphones, video recorders, LCD televisions, portable cleaners, portable CD players, mini-discs, transceivers, electronic notepads, calculators, memory cards, portable recorders, radios, backup power supplies, motors, cars, motorcycles, power-assisted bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, electric tools, flashlights, cameras, large household batteries or lithium-ion capacitors, etc.
[0126] 3. Embodiment
[0127] Hereinafter, the present application will be described in more detail with reference to Examples and Comparative Examples, but the present application is not limited to these Examples unless departing from the gist of the present application.
[0128] 1. Preparation of lithium-ion batteries
[0129] The preparation process of the lithium ion batteries of Comparative Example 1-1, Comparative Example 1-2, and Examples 1-1 to 1-21 is as follows:.
[0130] (1) Preparation of negative electrode
[0131] The negative electrode active material artificial graphite, the thickener sodium carboxymethyl cellulose (CMC), and the binder styrene butadiene rubber (SBR) are mixed in a weight ratio of 97:1:2, deionized water is added, and the negative electrode slurry is obtained under the action of a vacuum mixer, wherein the solid content of the negative electrode slurry is 54% by weight; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; the coated copper foil is dried at 85°C, and then cold pressed to obtain a negative electrode active material layer, and then cut and slit, and dried under vacuum conditions at 120°C for 12 hours to obtain a negative electrode.
[0132] (2) Preparation of positive electrode
[0133] Preparation of Li3PO4 modified positive electrode active material by liquid phase mixing method: 99 g LiNi 0.84 Co 0.13 Mn 0.06 O2 and 1 g of H3PO4 were dispersed in anhydrous ethanol by ultrasonication for 10 minutes, and then magnetically stirred for 60 minutes. Then, the mixture was transferred to an oil bath at 80°C and stirred until the ethanol was completely evaporated to obtain a Li3PO4-modified ternary positive electrode active material. The positive electrode active materials with different particle sizes were obtained by crushing and sieve screening.
[0134] The positive electrode active material LiNi modified by Li3PO4 0.84 Co 0.13 Mn 0.06 O2 (specific surface area 0.45m 3 / g), conductive agent Super P, and binder polyvinylidene fluoride are mixed in a weight ratio of 97:1.4:1.6, N-methylpyrrolidone (NMP) is added, and the mixture is stirred evenly under the action of a vacuum mixer to obtain a positive electrode slurry, wherein the solid content of the positive electrode slurry is 72% by weight; the positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil; the coated aluminum foil is dried at 85°C, and then cold pressed, cut, and slit, and then dried under vacuum conditions at 85°C for 4 hours to obtain a positive electrode. The positive electrode includes a positive electrode active material layer, which contains positive electrode active materials. Calculated based on the cross-sectional area of the positive electrode perpendicular to the direction of the aluminum foil, the sum of the cross-sectional areas of the first particles in the positive electrode accounts for 27.1% of the cross-sectional area, and the sum of the cross-sectional areas of the second particles in the positive electrode accounts for 37.8% of the cross-sectional area. The compaction density of the positive electrode active material layer is 3.4g / cm 3 .
[0135] The method for obtaining the compaction density is as follows: cut the electrode with a diameter of 18 mm, test the thickness of the disc with a micrometer, and weigh the mass of the disc. Compaction density = (mass of disc - mass of current collector in the disc) / (area of disc × (thickness of disc - thickness of current collector)).
[0136] (3) Preparation of electrolyte
[0137] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) were mixed in a mass ratio of EC: PC: EMC: DEC = 20: 10: 30: 40, and then additives were added. After dissolving and stirring thoroughly, lithium salt LiPF6 was added and mixed evenly to obtain an electrolyte. Among them, the concentration of LiPF6 is 1.10 mol / L. The specific types and contents of the additives used in the electrolyte are shown in Table 1. In Table 1, the content of the additives is calculated in grams per 1g of the modified positive electrode active material.
[0138] (4) Preparation of isolation membrane
[0139] A 9-micron thick polyethylene (PE) isolation membrane was selected, and the final isolation membrane was obtained after being coated and dried with polyvinylidene fluoride (PVDF) slurry and Al2O3 slurry.
[0140] (5) Preparation of lithium-ion batteries
[0141] The positive electrode sheet, the separator, and the negative electrode sheet are stacked in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role. Then, after winding and welding the pole ears, they are placed in the outer packaging foil aluminum-plastic film, and the prepared electrolyte is injected. After vacuum packaging, standing, formation, shaping, capacity testing and other processes, a soft-pack lithium-ion battery (thickness 3.3mm, width 39mm, length 96mm) is obtained.
[0142] Example 1-22: The electrolyte of the lithium ion battery was prepared according to the following method, and the other processes of the lithium ion battery preparation were exactly the same as those of Comparative Example 1-1.
[0143] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and compound II-3 are mixed in a mass ratio of EC: PC: EMC: DEC: compound II-3 = 20: 10: 40: 20: 10, and then additives are added, dissolved and stirred thoroughly, and then lithium salt LiPF6 is added, and the electrolyte is obtained after mixing evenly. Among them, the concentration of LiPF6 is 1.10 mol / L. The specific types and contents of the additives used in the electrolyte are shown in Table 1. In Table 1, the content of the additives is the gram weight required per 1g of the modified positive electrode active material.
[0144] Example 1-23: The electrolyte of the lithium ion battery was prepared according to the following method, and the other processes of the lithium ion battery preparation were exactly the same as those of Comparative Example 1-1.
[0145] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and compound II-3 are mixed in a mass ratio of EC: PC: EMC: DEC: compound II-3 = 20: 10: 20: 20: 30, and then additives are added, dissolved and stirred thoroughly, and then lithium salt LiPF6 is added, and the electrolyte is obtained after mixing evenly. Among them, the concentration of LiPF6 is 1.10 mol / L. The specific types and contents of the additives used in the electrolyte are shown in Table 1. In Table 1, the content of the additives is the gram weight required for each 1g of modified positive electrode active material.
[0146] Example 1-24: The electrolyte of the lithium ion battery was prepared according to the following method, and the other processes of the lithium ion battery preparation were exactly the same as those of Comparative Example 1-1.
[0147] In a dry argon atmosphere glove box, ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC) and compound II-2 are mixed in a mass ratio of EC: PC: EMC: DEC: compound II-2 = 20: 10: 30: 30: 10, and then additives are added, dissolved and stirred thoroughly, and then lithium salt LiPF6 is added, and the electrolyte is obtained after mixing evenly. Among them, the concentration of LiPF6 is 1.10 mol / L. The specific types and contents of the additives used in the electrolyte are shown in Table 1. In Table 1, the content of the additives is the gram weight required per 1g of positive electrode active material.
[0148] Example 1-25: The positive electrode of the lithium ion battery is prepared according to the following method, and the other processes of the lithium ion battery preparation are exactly the same as those of Comparative Example 1-1.
[0149] The positive electrode active material modified by Li3PO4 was prepared by sol-gel method: the positive electrode material (molecular formula LiNi 0.84 Co 0.13 Mn 0.06 91.7 g of LiPO4 was added to an ethanol solution containing 2 g of lithium nitrate, 5.4 g of citric acid and 0.9 g of phosphoric acid, and stirred vigorously to ensure that the mass ratio of the positive electrode material to Li3PO4 was 99:1. Then it was heated to 80°C and stirred continuously until the solvent evaporated completely, and finally calcined in an air atmosphere at 600°C for 2 hours to obtain a positive electrode active material modified with Li3PO4.
[0150] Example 1-26: The preparation process of the lithium-ion battery is exactly the same as that of Example 1-2, except that the compaction density of the positive electrode active material layer is 3.3 g / cm 3 .
[0151] Example 1-27: The preparation process of the lithium-ion battery is exactly the same as that of Example 1-2, except that the compaction density of the positive electrode active material layer is 3.6 g / cm 3 .
[0152] Example 1-28: The preparation process of the lithium-ion battery is exactly the same as that of Example 1-2, except that the sum of the cross-sectional areas of the first particles in the positive electrode active material accounts for 10.4% of the cross-sectional area.
[0153] Examples 1-29 to 1-31: The preparation process of the lithium-ion battery is exactly the same as that of Example 1-2, except that the positive electrode active material used is LiNi 0.84 Co 0.13 Mn 0.06 O2 is not modified with Li3PO4.
[0154] Example 1-32: The preparation process of the lithium-ion battery is exactly the same as that of Example 1-2, except that the positive electrode active material is LiNi 0.84 Co 0.13 Mn 0.058 Zr 0.002 O2.
[0155] Example 1-33: The preparation process of the lithium-ion battery is exactly the same as that of Example 1-2, except that the positive electrode active material is LiNi 0.84 Co 0.13 Mn 0.057 Al 0.001 Zr 0.002 O2.
[0156] Comparative Example 1-3: The preparation method is exactly the same as that of Comparative Example 1-1, except that the positive electrode active material used is LiNi 0.84 Co 0.13 Mn 0.06 O2 is not modified with Li3PO4.
[0157] Comparative Examples 2-1 to 2-4 and Examples 2-1 to 2-18: The battery preparation process is the same as that of Comparative Example 1-1, except for the type of positive electrode material and the electrolyte.
[0158] 2. Test methods for particle circularity, cross-sectional area and area ratio
[0159] (1) Particle roundness
[0160] The roundness of the positive electrode active material particles was tested using a roundness tester model DTP-550A.
[0161] (2) Particle cross-sectional area and area ratio
[0162] Using an ion polisher (model: JEOL-IB-09010CP), the positive electrode is cut perpendicular to the positive current collector to obtain a cross section. The above cross section is observed with a scanning electron microscope at an appropriate magnification, and pictures are taken using the backscatter mode. The function of the Image J software to identify the graphic morphology can identify the circularity and particle cross-sectional area, thereby identifying the particle A, the broken particles in the particle A, and the current collector. And the corresponding areas are identified accordingly. The total area of the positive electrode sheet cross section is S, the total area of the particle A is S1 (including broken particles), the total area of the broken particles in the particle A is S2, the area of the positive current collector is S3, the porosity is P, and the area ratio of the conductive agent and bonding is ignored. In the present application, the circularity of the particle A is greater than or equal to 0.4, and the cross-sectional area of a single particle A is greater than or equal to 20 square microns.
[0163] The total area of particle A = S1 / S × 100%;
[0164] The total area ratio of broken particles in particle A = S2 / S×100%;
[0165] The total area of the broken particles accounts for the total area of particle A = S2 / S1×100%;
[0166] The total area proportion of particle B = (S-S1-S3) / S×100%-P.
[0167] 3. Porosity test of positive electrode
[0168] The test was performed using a true density tester AccuPyc II 1340. Each sample was measured at least 3 times, and at least 3 data were selected to take the average value. The porosity P of the positive electrode was calculated according to the following formula: P = (V1-V2) / V1 × 100%, where V1 is the apparent volume, V1 = sample surface area × sample thickness × sample number; V2 is the true volume.
[0169] 4. Scanning electron microscope (SEM) test of lithium-ion battery positive electrode
[0170] After the lithium-ion battery reaches the full discharge state (i.e., discharged to a cut-off voltage of 2.8 V), the battery is disassembled to obtain the positive electrode, which is cleaned with DMC and vacuum dried, then cut along the direction of the positive electrode sheet, and the interface of the positive electrode active material is subjected to SEM testing.
[0171] 5. Cycle performance test of lithium-ion batteries
[0172] (1) Lithium-ion battery cycle performance test
[0173] Place the lithium-ion battery in a 45℃ constant temperature box and let it stand for 30 minutes to allow the lithium-ion battery to reach a constant temperature. Charge the lithium-ion battery that has reached a constant temperature at a constant current of 1C to a voltage of 4.2V, then charge it at a constant voltage of 4.2V to a current of 0.05C, and then discharge it at a constant current of 4C to a voltage of 2.8V. This is a charge and discharge cycle. With the capacity of the first discharge as 100%, repeat the charge and discharge cycle for 600 times, stop the test, and record the cycle capacity retention rate as an indicator for evaluating the cycle performance of the lithium-ion battery.
[0174] The cycle capacity retention rate refers to the capacity at 600 cycles divided by the capacity at the first discharge.
[0175] The cycle thickness change refers to the battery thickness at 600 cycles minus the initial battery thickness, and then divided by the initial battery thickness.
[0176] (2) High temperature storage performance test of lithium-ion batteries after cycling
[0177] The battery was charged to 4.2 V at a constant current of 1 C, and then the constant voltage was adjusted to a current of 0.05 C. The fully charged battery after cycling was placed in a 60°C constant temperature box and stored for 30 days, and the thickness change before and after storage was recorded.
[0178] Thickness change = (30-day storage thickness / initial thickness-1) × 100%.
[0179] A. Lithium ion batteries of Comparative Examples 1-1 to Comparative Examples 1-3 and Examples 1-1 to Examples 1-33 were prepared according to the above method, and the cycle performance and high temperature storage performance of the lithium ion batteries after cycling were tested. The test results of the amount of electrolyte added to the battery are shown in Table 1.
[0180] Table 1
[0181]
[0182] According to the comparison between Examples 1-1 to 1-5 and Comparative Examples 1-1 to 1-2, it can be seen that adding a specific content of the compound of formula I to the electrolyte can significantly improve the cycle performance and high temperature storage performance of the lithium-ion battery. The main reason may be that the compound of formula I can form a film on the surface of the positive electrode material and reduce the occurrence of side reactions.
[0183] According to the comparison between Examples 1-6 to 1-14 and Example 1-2, it can be seen that further adding a specific amount of additive A (such as LiPF2O2) to the electrolyte containing the compound of Formula I (such as at least one of Compounds 1-1, 1-2, 1-3 or 1-4) can further improve the cycle performance and high temperature storage performance of the lithium ion battery. The reason for this improvement may be that the additive A (such as LiPF2O2) preferentially forms a film on the surface of the negative electrode, improves the film structure, enhances the film stability, and is conducive to the compound of Formula I to play a greater role in the later stage of the cycle.
[0184] According to the comparison between Examples 1-15 to 1-20 and Example 1-9, it can be seen that further adding a specific amount of additive B to the electrolyte containing an appropriate amount of the compound of formula I and additive A (such as LiPF2O2) can further improve the cycle performance and high temperature storage performance of the lithium ion battery; according to the comparison between Example 1-21 and Example 1-2, it can be seen that further adding a specific amount of additive B to the electrolyte containing an appropriate amount of the compound of formula I can further improve the cycle performance and high temperature storage performance of the lithium ion battery. The main reason may be that additive B has a film-forming effect on the negative electrode during the formation stage, thereby enhancing the interface stability of the negative electrode.
[0185] According to the comparison between Examples 1-22 to 1-24 and Example 1-16, it can be seen that the addition of a specific amount of the compound of Formula II to the electrolyte containing an appropriate amount of the compound of Formula I, the additive A and the additive B can further improve the cycle performance and high temperature storage performance of the lithium ion battery. The main reason may be that on the one hand, the compound of Formula II reduces the viscosity of the electrolyte, and on the other hand, the combination of additives changes the film structure of the positive electrode surface, thereby improving the film stability.
[0186] By comparing Example 1-25 with Example 1-2, it can be seen that the performance of the positive electrode active materials modified by liquid phase mixing and sol-gel method are similar, and both methods are suitable for the modification application of positive electrode active materials.
[0187] Comparison of Examples 1-26 and 1-27 with Example 1-2 shows that reducing the compaction density of the positive electrode active material layer can improve the cycle performance and high temperature storage performance. This may be because the appropriate compaction density can reduce the degree of particle crushing of the material; increasing the compaction density is the opposite. Considering the requirements of mass energy density and volume energy density in practical applications, the compaction density <3.6g / cm 3 Suitable for practical applications.
[0188] By comparing Example 1-28 with Example 1-2, it can be seen that controlling the proportion of the first particles in the positive electrode active material can alleviate the side reactions caused by particle breakage in the late cycle, which is beneficial to improving the cycle performance and high-temperature storage performance.
[0189] By comparing Example 1-29 with Example 1-2, it can be seen that the stability of the positive electrode material after Li3PO4 modification is improved, the side reaction between the electrolyte and the positive electrode is effectively reduced, and the cycle performance of the battery is improved.
[0190] By comparing Examples 1-31 and 1-30 with Example 1-29, it can be seen that when the positive electrode active material is not modified with Li3PO4, further adding additives A (such as LiPF2O2) and additives B to the electrolyte containing an appropriate amount of the compound of formula I can further improve the cycle performance and high temperature storage performance of the lithium-ion battery.
[0191] By comparing Examples 1-33 and 1-32 with Example 1-2, it can be seen that further inclusion of Q element in the positive electrode active material can further improve the cycle performance and high-temperature storage performance of the battery.
[0192] B. Lithium ion batteries of Comparative Examples 2-1 to Comparative Examples 2-4 and Examples 2-1 to 2-18 were prepared according to the above method, and the cycle performance and high temperature storage performance of the lithium ion batteries after cycling were tested. The positive electrode active materials, electrolytes and test results are shown in Table 2. The cross-sectional area ratio of the first particles to the second particles in the positive electrode active material is achieved by controlling the mass ratio of the first particles to the second particles.
[0193] Table 2
[0194]
[0195] According to the comparison between Comparative Examples 2-1 to Comparative Examples 2-4 and Examples 2-1 to Examples 2-4, it can be seen that the use of various nickel-rich positive electrode materials modified by Li3PO4 in the battery and the addition of the compound of formula I in the electrolyte can stabilize the material structure, stabilize the interface with the electrolyte, reduce side reactions, and further improve the cycle performance and high-temperature storage performance of the lithium-ion battery. It can be further seen from Examples 2-5 to 2-9 and Examples 2-11 to 2-13 that the use of various nickel-rich positive electrode materials modified by Li3PO4 and the addition of the compound of formula I and additive A (such as LiPO2F2) in the electrolyte can further improve the cycle performance and high-temperature storage performance of the lithium-ion battery. The main reason may be that after the addition of additive A, the film formation impedance is relatively small, the DC internal resistance of the battery can be reduced, and the side reactions of the electrolyte on the positive electrode surface can be reduced.
[0196] From the comparison between Examples 2-15 to 2-18 and Example 1-32, it can be seen that when the nickel content in the positive electrode active material is high, especially when the nickel molar content is not less than 60%, the number of first particles and the number of second particles in the positive electrode material are within a suitable range, which is beneficial to the improvement of cycle performance and gas production.
[0197] Without wishing to be bound by any theory, the present invention finds that adding a positive electrode film-forming additive formula I compound (e.g., 1,3-propane sultone (PS)) to the electrolyte can improve interface stability and reduce side reactions; in addition, it is found that the use of spherical secondary particle grain boundary modification can significantly inhibit the particle breakage during the cycle of nickel-rich ternary positive electrode materials and improve the material structure stability. The use of additive A (e.g., LiPO2F2) in the electrolyte can lead to the solid electrolyte interface film (SEI) formed at the positive electrode having a fast ion conduction effect, which is beneficial to reduce the direct current resistance (DCR), increase the inorganic components in the electrode interface film, thereby enhancing the stability of the interface protective layer, and also protect the positive electrode interface. Smaller primary particles in the positive electrode material are beneficial to shorten the ion transmission distance and improve the rate performance of the material. Smaller primary particles will increase the specific surface area of the material and increase the consumption of the film-forming additive. Further introduction of a formula II compound (e.g., a fluorinated solvent) into the electrolyte can increase the electrolyte stability and reduce the reaction of the solvent on the surface of the material. By combining the positive electrode material grain boundary modification with the electrolyte positive electrode protection additive, the particle size and specific surface area of the positive electrode material can be limited, which can ensure the battery rate performance while effectively improving the high-temperature storage and high-temperature cycle of the spherical secondary particle nickel-rich ternary material battery system, and solve the technical problem of high-temperature cycle gas production.
[0198] C. Scanning electron microscopy (SEM) testing of positive electrode active materials
[0199] The positive electrode active material of Comparative Example 1-1 (LiNi modified by Li3PO4) 0.84 Co 0.13 Mn 0.06 O2) was tested by scanning electron microscope, and the results were as follows Figure 1 shown.
[0200] Figure 1 The left picture in the middle is a SEM picture of the positive electrode active material, and the right picture is a distribution diagram of the phosphorus content in the SEM picture. It can be seen from the right picture that the phosphorus element in the form of gray dots is distributed on the surface or grain boundary of the positive electrode active material.
[0201] The SEM test results of the modified positive electrode active materials in other embodiments are similar to those in Figure 1 similar.
[0202] The above are only several embodiments of the present invention and are not intended to limit the present invention in any form. Although the present invention is disclosed as above in the form of a preferred embodiment, it is not intended to limit the present invention. Any technician familiar with the profession, without departing from the scope of the technical solution of the present invention, using the above disclosed technical content to make slight changes or modifications are equivalent to equivalent implementation cases and fall within the scope of the technical solution.
[0203] References to "some embodiments", "partial embodiments", "one embodiment", "another example", "example", "specific example" or "partial example" throughout the specification mean that at least one embodiment or example in the present application includes the specific features, structures, materials or characteristics described in the embodiment or example. Therefore, descriptions appearing in various places throughout the specification, such as: "in some embodiments", "in an embodiment", "in another example", "in an example", "in a specific example" or "example", do not necessarily refer to the same embodiment or example in the present application. In addition, the specific features, structures, materials or characteristics herein may be combined in one or more embodiments or examples in any suitable manner. Although illustrative embodiments have been demonstrated and described, those skilled in the art should understand that the above embodiments cannot be interpreted as limitations on the present application, and that the embodiments may be changed, substituted and modified without departing from the spirit, principles and scope of the present application.
Claims
1. An electrochemical device comprising a positive electrode, a negative electrode, a separator and an electrolyte, wherein The positive electrode comprises a current collector and a positive electrode active material layer, wherein the positive electrode active material layer comprises a positive electrode active material, wherein the surface or grain boundary of the positive electrode active material comprises a phosphorus-containing compound, wherein the phosphorus-containing compound comprises at least one of Li3PO4 or LiMPO4, wherein M is selected from at least one of Co, Mn or Fe; The electrolyte contains a compound of formula I: , Where R 11 , R 12 , R 13 , R 14 , R 15 and R 16 Each is independently selected from: H, halogen, substituted or unsubstituted groups: C 1-8 Alkyl, C 2-8 Alkenyl, C 2-8 Alkynyl, or C 6-12 aryl; and Additive B, wherein the additive B comprises at least one of vinylene carbonate, fluoroethylene carbonate, vinyl sulfate, tris(trimethylsilyl)phosphate, tris(trimethylsilyl)borate, adiponitrile, succinonitrile, 1,3,5-pentanetricarboxylate, 1,3,6-hexatricarboxylate, 1,2,6-hexatricarboxylate, or 1,2,3-tris(2-cyano)propane. 2 . The electrochemical device according to claim 1 , wherein the amount of the compound of formula (I) required per 1 g of the positive electrode active material is 0.001 g to 0.064 g.
3. The electrochemical device according to claim 1, wherein the compound of formula I comprises at least one of the following compounds: 。 4. An electrochemical device according to claim 1, wherein the positive electrode active material layer comprises first particles, the circularity of the first particles is 0.4 to 1, wherein the cross-sectional area of the first particles is not less than 20 square microns, calculated based on the cross-sectional area of the positive electrode perpendicular to the current collector, and the sum of the cross-sectional areas of the first particles accounts for 5% to 50%.
5. An electrochemical device according to claim 4, wherein the positive electrode active material layer comprises second particles, and the circularity of the second particles is less than 0.4; wherein the cross-sectional area of the second particles is smaller than the cross-sectional area of the first particles, calculated based on the cross-sectional area of the positive electrode perpendicular to the current collector, and the sum of the cross-sectional areas of the second particles accounts for 5% to 60%.
6. The electrochemical device according to any one of claims 1 to 5, wherein the electrolyte further comprises an additive A, wherein the additive A comprises at least one of LiBF4, LiPO2F2, LiFSI, LiTFSI, 4,5-dicyano-2-trifluoromethylimidazolium lithium, lithium difluorobis(oxalato)phosphate, lithium difluorooxalatoborate, or lithium bis(oxalatoborate).
7. The electrochemical device according to claim 6, wherein: 0.000026 g to 0.019 g of the additive A is required per 1 g of the positive electrode active material.
8. The electrochemical device according to claim 1, wherein The mass ratio of the compound of formula I to the additive B is 7:1 to 1:
7.
9. The electrochemical device according to claim 1, wherein: 0.0001 g to 0.2 g of the additive B is required per 1 g of the positive electrode active material.
10. The electrochemical device according to claim 1, wherein the positive electrode active material comprises LiNi x Co y Mn z O2, of which 0.55 <x<0.92,0.03<y<0.2,0.04<z<0.3。 11. The electrochemical device according to claim 1, wherein the compaction density of the positive electrode active material layer is less than or equal to 3.6 g / cm 3 .
12. The electrochemical device according to claim 1, wherein the electrolyte further comprises a compound of formula II , where R 31 and R 32 Each independently selected from substituted or unsubstituted C 1-10 Alkyl, or substituted or unsubstituted C 2-8 Alkenyl, wherein substituted refers to substituted by one or more halogens; based on the total weight of the electrolyte, the content of the compound of formula II is 0.5 wt % to 50 wt %.
13. The electrochemical device according to claim 12, wherein the compound of formula II comprises at least one of the following compounds: 。 14. An electronic device comprising the electrochemical device according to any one of claims 1 to 13.
Citation Information
Patent Citations
Electrolyte additive and use thereof in lithium-ion battery
US9812739B2
Electrochemical device
CN110165219A
Electrode for battery, manufacturing method thereof, and battery
JP2009283353A